Reconstrução histórica da fauna marinha e da paisagem recifal brasileira - Fogliarini, Carine de Oliveira (2022)
Human impacts have drastically altered marine ecosystems for thousands of years. This millenary influence makes difficult our understanding the past state of these environments and makes it impossible to form a more complete overview of the diversity patterns observed in the oceans nowadays. Historical records including nautical charts, naturalist reports, old paintings, photographs, and fisher knowledge have provided information to quantify long-term ecological changes in the oceans. The main objective of this thesis was to reconstruct the state of the marine fauna and reef seascape at different spatial and temporal scales, and it covers four chapters, whose specific objectives were: (i) to investigate temporal changes in target species of artisanal fisheries through interviews with fishers in Arraial do Cabo city, Rio de Janeiro state; (ii) to estimate possible changes in spatial extent of reefs in the Abrolhos Bank, Bahia state; (iii) to identify changes in the richness, distribution and functional structure of coral assemblages throughout the Brazilian Province; and (iv) to estimate historical changes in the patterns of distribution, abundance, and size of individuals of marine vertebrate species along the Brazilian coast. In the first chapter, interviews with fishers revealed variations in the perception associated with the state of exploitation of fishing resources over time in Arraial do Cabo. In addition, temporal analysis of local landing data revealed a 72% decline in meso-predator catches. The depletion of meso-predators led to the replacement of target species: fish that were previously discarded became new target of fishing. In the second chapter, naturalist records and comparisons between a 160-year-old nautical chart and satellite images revealed declines from 19% to 49% in the spatial extent of reefs in the Abrolhos Bank. Reef declines are linked to cumulative impacts such as coral extraction for lime and coastal sedimentation recorded over the last 200 years. In the third chapter, the analysis of naturalist accounts showed an increase in the number of coral records since the mid-1800s throughout the Brazilian Province. Nevertheless, declines in functional divergence of coral assemblages in the Abrolhos Bank were related to reductions in the abundance of two major reef builder corals Millepora alcicornis and Mussismilia braziliensis. In the fourth chapter, we reconstruct five centuries of marine vertebrate exploration through the analysis of naturalist accounts, paintings, engravings, and fishing reports. Historical accounts contrasted with landing data revealed declines in catches of whale, manatee, and grouper since the 17th century on the Brazilian coast. In addition, historical information suggests that target species had larger average body sizes than currently recorded, as detected for the manatee (Trichechus sp.), Atlantic tarpon (Megalops atlanticus), and cobia (Rachycentron canadum). The rebuilt history in this thesis consists of the first formal effort to define a reference (‘baseline’) of the past and present state of marine resources explored on the Brazilian coast. This historical reconstruction of marine fauna provides a more solid basis for initiatives aimed at conservation and restoration of the Brazilian reef ecosystems.